Profiles of attendees in voluntary counseling and testing centers of a medical college hospital in coastal Karnataka - Jayarama S; Shenoy Shaliny; Unnikrishnan B; Ramapuram John; Rao Manjula (Wolters Kluwer Medknow Publications, 2008)
Research Question: What are the socio-demographic profile and risk behavior pattern of seropositive attendees in the voluntary counseling and testing center (VCTC)? Study Design: Retrospective study. Setting: VCTC in the outpatient complex of Kasturba Medical College Hospital, Mangalore, Karnataka. Subjects: Records pertaining to all the 539 and 330 seropositive attendees during the years 2005 and 2006, respectively, were included in the study besides data from 2001 onwards in order to assess the time trend of human immunodeficiency virus (HIV). Study Variables: Age, sex, marital status, religion, educational status, occupation, place of residence and pattern of risk behavior in relation to HIV/AIDS. Statistical Analysis: Analysis was done with SPSS version 11. Statistical test and Chi-square was done, and P < 0.05 was considered statistically significant. Results: The time trend of VCTC attendees reveals a gradual increase except in 2006 showing a sharp decline. Seropositives were around 20% between 2001 and April 2007 with a sharp increase in 2006, i.e., 33.64%. Male seropositivity constituted 60-63%; 81-91% of seropositive attendees belonged to the age group of 15-50 years; 58-70% were married. Only about 3% were illiterates and 20-25% constituted 6 th -12 th pass-outs. With regard to occupational profile, about 17-27% were housewives, 19-21% were laborers/hotel workers and 7% were entrepreneurs. About 45% were from urban area and nearly one-third hailing from other districts in the border of Karnataka. About 25% were exposed to commercial sex workers; another 21-23% were involved in premarital sex and nearly 38% were indulging in heterosexual activities.